Tissue Factor and Cancer: Regulation, Tumor Growth, and Metastasis - Hisada, Yohei; Mackman, Nigel (Seminars in Thrombosis and Hemostasis, 2019)
There is a strong relationship between tissue factor (TF) and cancer. Many cancer cells express high levels of both full-length TF and alternatively spliced (as) TF. TF expression in cancer is associated with poor prognosis. In this review, the authors summarize the regulation of TF expression in cancer cells and the roles of TF and asTF in tumor growth and metastasis. A variety of different signaling pathways, transcription factors and micro ribonucleic acids regulate TF gene expression in cancer cells. The TF/factor VIIa complex enhances tumor growth by activating protease-activated receptor 2 signaling and by increasing the expression of angiogenic factors, such as vascular endothelial growth factor. AsTF increases tumor growth by enhancing integrin β1 signaling. TF and asTF also contribute to metastasis via multiple thrombin-dependent and independent mechanisms that include protecting tumor cells from natural killer cells. Finally, a novel anticancer therapy is using tumor TF as a target to deliver cytotoxic drugs to the tumor. TF may be useful in diagnosis, prognosis, and treatment of cancer.
Keywords: cancer; metastasis; thrombosis; tissue factor; tumor